The Improving Si0.5Ge0.5/Si Interface Quality through a Low Energy Hydrogen Plasma Cleaning Process and Positron Annihilation Spectroscopy (International Journal of Automation and Smart Technology, 2014)
Positron Annihilation Spectra (PAS), Raman, and photoluminescence spectroscopy reveal that Si0.5Ge0.5/Si interface quality can be dramatically improved through a low energy plasma cleaning process using hydrogen. In the PAS, the particularly small values of lifetime and intensity near the Si0.5Ge0.5/Si interface in the treated sample indicate a 2.25 times reduction in defect concentration. Fewer defects were found in the interface, resulting in a high compressive strain of about 0.36 % in the top layer, which can be observed in Raman spectra, and a 1.39 times increase to the radiative recombination rate for the infrared emission, which can be observed in the photoluminescence spectra. Improved Si0.5Ge0.5/Si interface quality leads to improved optical and electrical characteristics in SiGe-based devices in a broader range of photovoltaic applications. The PAS is also shown to be a useful metrology tool for quantifying defects in SiGe-based devices